1998
DOI: 10.1006/viro.1998.9433
|View full text |Cite
|
Sign up to set email alerts
|

Oncosis in MA104 Cells Is Induced by Rotavirus Infection through an Increase in Intracellular Ca2+Concentration

Abstract: Rotavirus infection modifies the metabolism and ionic homeostasis of the host cell. First, there is an induction of viral synthesis with a parallel shutoff of cell protein production, followed by an increase of plasma membrane Ca2+ permeability, thereby inducing an increase of free cytoplasmic and sequestered Ca2+ concentrations. Cell death follows at a later stage. We studied the role of the increase in Ca2+ concentration in cell death. An elevation of extracellular Ca2+ concentration during infection induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 25 publications
4
33
1
2
Order By: Relevance
“…This disruption of Ca 2ϩ homeostasis appears to be mediated by synthesis of viral proteins (17,49). Increased Ca 2ϩ permeability at both the plasma membrane and the endoplasmic reticulum leads to an increase in [Ca 2ϩ ] i , triggering a chain of events that leads to cell lysis (61 (19). In contrast, the increase in [Ca 2ϩ ] i induced by intracellular NSP4 is independent of PLC stimulation (73).…”
Section: The Molecular Basis Of Diarrhea Inductionmentioning
confidence: 99%
“…This disruption of Ca 2ϩ homeostasis appears to be mediated by synthesis of viral proteins (17,49). Increased Ca 2ϩ permeability at both the plasma membrane and the endoplasmic reticulum leads to an increase in [Ca 2ϩ ] i , triggering a chain of events that leads to cell lysis (61 (19). In contrast, the increase in [Ca 2ϩ ] i induced by intracellular NSP4 is independent of PLC stimulation (73).…”
Section: The Molecular Basis Of Diarrhea Inductionmentioning
confidence: 99%
“…However, for differentiated polarized cells, alternative modes of virion release without cell lysis have been proposed (11). Ca 2ϩ is known to control many key cell processes, and thus, its concentration within the cell is tightly regulated (6 homeostasis is concomitant with the onset of TPL assembly in the ER (24,28). Alterations in cell Ca 2ϩ homeostasis have been related to cytotoxicity and cell death, since the prevention or reduction of these changes results in a delay in cell death (28).…”
Section: Rotavirus Infection Of Cells In Culture Induces Major Changementioning
confidence: 99%
“…Ca 2ϩ is known to control many key cell processes, and thus, its concentration within the cell is tightly regulated (6 homeostasis is concomitant with the onset of TPL assembly in the ER (24,28). Alterations in cell Ca 2ϩ homeostasis have been related to cytotoxicity and cell death, since the prevention or reduction of these changes results in a delay in cell death (28). Furthermore, alterations in Ca 2ϩ homeostasis may be part of the basis of physiologic alterations in the intestine caused by rotavirus infection which finally lead to diarrhea (16,26).…”
Section: Rotavirus Infection Of Cells In Culture Induces Major Changementioning
confidence: 99%
“…An increase of the intracellular sequestered Ca 2ϩ pools has also been measured (26,27). The effect of viral protein synthesis on [Ca 2ϩ ] i homeostasis may be responsible for cytopathic effect and cell death (26,29). Tian et al (35,36) have reported that the expression of the rotavirus nonstructural protein NSP4 increases [Ca 2ϩ ] i in Spodoptera frugiperda (Sf9) cells.…”
Section: ؉ -Dependent Microvillar F-actin Alteration In Uninfected Cmentioning
confidence: 99%